THE DESIGN OF SPENCER GENERIC COMPETENCY AS A MODEL FOR BANKING SUPERVISORS POSITION SPECIFICATION IN SURABAYA - Irawan Irawan (Journal of Economics, Business, and Accountancy Ventura, 2011)
Banking industries have some targets in which the supervision of banks is required. In orderthat the banks can strengthen the national banking industry fundamental, Bank Indonesia(BI) implements Indonesia Banking Architecture (IBA). The second target of the ABI is tocreate a system of independent and effective bank regulation and supervision based on internationalstandards. This study attempts to uncover some issues such as (1) How to designgeneric competencies of Spencer as a model specification for the Supervision of Banking officesin Surabaya; (2) How technical competence and perceived behavioral competencies ascompetencies are required for Banking Supervision. This study uses 50 bank branch managersin Surabaya as respondents. Descriptive analysis is applied for analyzing the data. Basedon such analysis, it can be concluded that, first of all, the design of generic competencies ofSpencer can be used as a model specification for the position of Banking Supervisors in Surabaya.This can be done according to the order level based on the perception of importanceby the respondents in which the expertise in the field of task is in the first place. Secondly, thetechnical competencies and behavioral competency that are perceived as competencies requiredfor Banking Supervision acting in Surabaya are the competency to analyze the coreproblem.